KORELASI KUALITAS DIET DENGAN KUALITAS HIDUP PADA PENYINTAS COVID-19 DI KABUPATEN BANYUMAS - Baiti Kinasih; Ani Margawati; Annastasia Ediati (Journal of Nutrition College, 2026)
ABSTRACTBackground: The COVID-19 pandemic has had a significant impact on the global population and various aspects of life. Although the infection can be cured, COVID-19 may cause long-term effects on the health of patients who have been declared virus-free. The quality of life of COVID-19 survivors has been reported to remain relatively low. Nutritional factors could play a role in the recovery process.Objectives: evaluating the correlation between diet quality and quality of life in COVID-19 survivors.Methods: a cross-sectional study involving 96 COVID-19 survivors aged over 18 years was conducted in Banyumas Regency, Central Java. Data collection took place two years following the post-infection phase. Quality of life was assessed using the Indonesian version of the WHOQOL-BREF. Diet quality was measured using the Diet Quality Index-International (DQI-I). We evaluated dietary intake using SQ-FFQ and analyzed it with NutriSurvey software. Pearson and Spearman correlation tests were applied to analyze the data, using IBM Statistic SPSS version 23.Results The physical and psychological domains of quality of life among COVID-19 survivors had lower median scores compared to the social and environmental domains. Most of survivors (83.3%) had poor diet quality. Intake of vegetables, fiber, and calcium was below daily recommendations, while fat intake was excessive, resulting in an imbalance in macronutrient and micronutrient ratios. There was a positive correlation between overall diet quality scores, including dietary diversity, nutrient adequacy (particularly fruit and fiber intake), and nutrient balance. Conversely, intake of total fat, saturated fat, cholesterol, and empty calorie foods showed a negative correlation with quality of life.Conclusion: Nutrient intake plays a contributory role in the rehabilitation process of COVID-19 survivors. Greater attention should be given to the dietary patterns and types of foods consumed by this population.Keywords : diet quality; nutrition; quality of life; COVID-19 survivor. ABSTRAKLatar belakang: pandemi COVID-19 berdampak besar terhadap populasi dunia dan berbagai aspek kehidupan. Meskipun bisa disembuhkan, infeksi COVID-19 dapat menimbulkan efek jangka panjang pada kesehatan pasien yang dinyatakan terbebas dari virus. Kualitas hidup penyintas COVID-19 dilaporkan masih tergolong rendah. Faktor gizi mungkin berperan dalam proses penyembuhan penyakit. Tujuan: mengevaluasi korelasi kualitas diet dengan kualitas hidup pada penyintas COVID-19.Metode: studi potong lintang yang melibatkan 96 partisipan berusia >18 tahun. Penelitian dilakukan di Kabupaten Banyumas, Jawa Tengah, pada penyintas COVID-19 pascainfeksi 2 tahun. Kualitas hidup dinilai dengan WHOQOL-BREF versi Indonesia. Kualitas diet diukur dengan Diet Quality Index International (DQI-I). Asupan makanan dihitung dengan instrumen SQ-FFQ dengan bantuan software nutrisurvey. Uji korelasi pearson dan spearman digunakan untuk analisis data, dengan bantuan software IBM Statistic SPSS 23.Hasil: kualitas hidup penyintas COVID-19 pada domain fisik dan psikis memiliki median yang lebih rendah dari domain sosial dan lingkungan. Kualitas diet penyintas COVID-19 sebagian besar (83,3%) tergolong rendah. Asupan sayur, serat, dan kalsium kurang dari rekomendasi harian. Asupan lemak responden tinggi, sehingga rasio asupan makronutrien dan mikronutrien tidak seimbang. Terdapat korelasi positif antara skor total kualitas diet, keragaman pangan, kecukupan asupan zat gizi yang berasal dari asupan buah dan serat, dan keseimbangan zat gizi, dengan kualitas hidup penyintas COVID-19. Sebaliknya, asupan lemak total, lemak jenuh, kolesterol, dan makanan rendah gizi, berkorelasi negatif dengan kualitas hidup.Simpulan: asupan zat gizi terbukti berkontribusi terhadap proses rehabilitasi penyintas COVID-19. Perlu adanya perhatian lebih pada pola makan dan jenis asupan yang dikonsumsi penyintas COVID-19.Kata Kunci : Kualitas diet; gizi; kualitas hidup; penyintas COVID-19